Anti-AMPA receptor encephalitis associated with Medullary thyroid cancer. (27th August 2018) - Samad, Navira; Wong, Jennifer
Abstract : AMPA receptor (AMPAR) antibodies are a group of recently discovered antibodies which target the neuronal synaptic proteins causing B-cell (immune) mediated neuronal damage, resulting in various neurologic syndromes depending on the area of central nervous system involvement. These syndromes are mostly reversible if treated early. Tumour association has been reported in up to 60% of cases in the most recent case series with lung, breast, ovarian cancers and thymomas being the most commonly associated malignancies with these antibodies. We present here the first case of AMPAR encephalitis associated with medullary thyroid cancer. Our patient presented with cognitive dysfunction and behavioural changes over a period of 3 weeks, with a full recovery after starting immunotherapy, once the diagnosis of AMPAR limbic encephalitis was established. This case highlights the importance of early diagnosis and management of AMPAR encephalitis as these patients respond well to immunotherapy and can have an almost complete recovery.